'Candidatus Ornithobacterium hominis': insights gained from draft genomes obtained from nasopharyngeal swabs. Issue 2 (5th February 2019) - Salter, Susannah J.; Scott, Paul; Page, Andrew J.; Tracey, Alan; de Goffau, Marcus C.; Cormie, Claire; Ochoa-Montaño, Bernardo; Ling, Clare L.; Tangmanakit, Jiraporn; Turner, Paul; Parkhill, Julian
Abstract : ' Candidatus Ornithobacterium hominis' represents a new member of the Flavobacteriaceae detected in 16S rRNA gene surveys of people from South-East Asia, Africa and Australia. It frequently colonizes the infant nasopharynx at high proportional abundance, and we demonstrate its presence in 42 % of nasopharyngeal swabs from 12-month-old children in the Maela refugee camp in Thailand. The species, a Gram-negative bacillus, has not yet been cultured, but the cells can be identified in mixed samples by fluorescent hybridization. Here, we report seven genomes assembled from metagenomic data, two to improved draft standard. The genomes are approximately 1.9 Mb, sharing 62 % average amino acid identity with the only other member of the genus, the bird pathogen Ornithobacterium rhinotracheale . The draft genomes encode multiple antibiotic-resistance genes, competition factors, Flavobacterium johnsoniae - like gliding motility genes and a homologue of the Pasteurella multocida mitogenic toxin. Intra- and inter-host genome comparison suggests that colonization with this bacterium is both persistent and strain exclusive.